1995
DOI: 10.1084/jem.182.2.305
|View full text |Cite|
|
Sign up to set email alerts
|

Cloning and characterization of 5E6(Ly-49C), a receptor molecule expressed on a subset of murine natural killer cells.

Abstract: 5E6 is a cell surface molecule expressed on a subpopulation of murine natural killer (NK) cells that are involved in the specific rejection of H-2d or H-2f (hemopoietic histocompatibility determinant 2) bone marrow cell grafts. Here, we isolated and cloned the gene encoding 5E6 and determined the nucleotide sequence of the cDNA. 5E6 is nearly identical to Ly-49C; the deduced amino acid sequence reveals a polypeptide of 266 amino acids with a molecular weight of 31,284 that contains multiple cysteine residues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 34 publications
2
73
0
Order By: Relevance
“…These results indicate that phosphorylation of the tyrosine residue in the ITIM is necessary for recruitment of SHP-1 and SHP-2 to Ly49Q. Thus, Ly49Q expressed on COS7 cells shows biochemical characteristics similar to other known Ly49 family members (12,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…These results indicate that phosphorylation of the tyrosine residue in the ITIM is necessary for recruitment of SHP-1 and SHP-2 to Ly49Q. Thus, Ly49Q expressed on COS7 cells shows biochemical characteristics similar to other known Ly49 family members (12,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 55%
“…2B). Under nonreducing conditions, FLAG-tagged Ly49Q showed an apparent molecular mass of 130 and 220 kDa, indicating that Ly49Q is expressed as dimer or oligomer on the cell surface as in case of other Ly49 family members (27,28). Ly49Q appeared to be N-glycosylated because the treatment with N-glycosidase F reduced its apparent molecular mass (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ly-49A binds the class I molecules H-2D d , D k , and D p , and Ly-49G2 binds H-2D d and H-2L d . [37][38][39][40][41] These bindings mediate a negative signal to the NK cells, resulting in inhibition of lysis. Recent studies have suggested that these members of the Ly-49 family may also interact with H-2 b molecules.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Cloning and sequencing of Ly49 cDNAs showed that BALB/c NK cells share at least three Ly49-related sequences or alleles with B6 mice: Ly49a, c, and g, although the alleles have diverged and contain a significant number of differences, resulting in several amino-acid substitutions. [6][7][8] The novel activating Ly49L receptor was also found to be expressed in BALB/c mice, but was first identified in the Ly49 haplo-identical CBA and C3H mouse strains. 8,9 The finding of Ly49L supported the contention that all activating receptors have an inhibitory counterpart with a highly similar extracellular domain that has probably arisen by gene hybridization between two different Ly49 genes.…”
Section: Introductionmentioning
confidence: 99%